Penerapan RFID (Radio Frequency Identification) di Perpustakaan: Kelebihan dan Kekurangannya - Hamdani, Fadhilatul (Program Studi Ilmu Perpustakaan UIN Alauddin, 2014)
Library is a dynamic organization and always change according to the times. With the development of information technology, libraries must change the way it works to be more advanced, efficient and effective. One application of the latest technology in libraries is using RFID technology, which has two main functions, namely identification and security of library materials. In addition to having several advantages, RFID also has some shortcomings when it will be implemented in the library. Application of RFID in libraries is expected to maximize the performance and service libraries.